Fs laser-induced filament study of aliphatic nitroalkanes: correlation between molecular structure and spectroscopic evolution of the filament. Issue 5 (10th February 2022) - Zhao, Y. L.; Deng, K.; Shi, J. C.
Abstract : fs laser-induced filament and breakdown spectroscopy can be used for studying the correlation between the molecular structure and spectroscopic evolution of the filament. Abstract : Three aliphatic nitroalkanes, nitromethane, nitroethane, and 1-nitropropane, are investigated with fs laser-induced filament and breakdown spectroscopy (LIFBS). Filament emission spectra, C I, the CN violet system (B 2 Σ + − X 2 Σ +, Δ ν = 0 sequence), and the C2 swan system (d 3 Πg − a 3 Πu, Δ ν = 0 sequence), are obtained. The time integrated intensities of CN and C2 can be used for identifying the three nitroalkanes. The filament features (length, diameter, and temperature) of the CN and C2 emissions are analyzed; C2 converts to CN through a single-atom substitution reaction between C2 and N atoms at the early stage, which mainly occurs at the head and tail parts of the filament with a lower temperature rather than at the hotter middle part.